2016
DOI: 10.2151/jmsj.2016-029
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Evolution of Misovortices Observed within a Convective Snowband in the Japan Sea Coastal Region during a Cold-Air Outbreak on 31 December 2007

Abstract: Cyclonic misovortices with a horizontal scale of 0.4 -1.9 km embedded within a convective snowband were observed by two X-band Doppler radars in the Japan Sea coastal region on December 31, 2007, during a cold-air outbreak. All vortices initially developed offshore, subsequently making a landfall. The structure and temporal evolution of these vortices during the landfall were investigated using high-resolution data obtained from two X-band Doppler radars.The studied vortices developed along a low-level converg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Among those studies, Kobayashi et al (2007) documented a radar-observed misocyclone within a parent cloud over the Sea of Japan and a visible waterspout funnel cloud connected to its cloud base. Inoue et al (2011), Inoue et al (2016), and Onomura et al (2017) pointed out that misocyclones have been associated with wind gusts which were confirmed by damage surveys and/or surface wind observations. Kusunoki et al (2017) investigated the vertical structure of a landfalling misocyclone at about 100-1000 m above the surface.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Among those studies, Kobayashi et al (2007) documented a radar-observed misocyclone within a parent cloud over the Sea of Japan and a visible waterspout funnel cloud connected to its cloud base. Inoue et al (2011), Inoue et al (2016), and Onomura et al (2017) pointed out that misocyclones have been associated with wind gusts which were confirmed by damage surveys and/or surface wind observations. Kusunoki et al (2017) investigated the vertical structure of a landfalling misocyclone at about 100-1000 m above the surface.…”
Section: Introductionmentioning
confidence: 61%
“…Recent observations with Doppler radars on the Sea of Japan revealed the existence of circulations aloft that were associated with wind gusts or waterspouts in winter (Kobayashi et al 2007;Inoue et al 2011;Inoue et al 2016;Kusunoki et al 2017;Onomura et al 2017). The circulations in those studies were referred to as misocyclones since their dimensions were less than 4 km (i.e., circulations with a diameter between 40 m and 4 km; Fujita 1981).…”
Section: Introductionmentioning
confidence: 99%